Summer thoughts / Elliza Hashim - Hashim, Elliza (Faculty of Art and Design, 2021)
Colors and textures intoxicate our minds with memories that remind us of feelings that evoke happiness, curiosity, fear, longing, hope and so on. And these memories are a woven of thoughts that explains to us in whichever way that is unique to an individual. What the eyes can see can be a trick to the mind, what appears to be 2D but in fact is 3D. We wonder, do we trust our eyes or our minds to make sense of reality? Perhaps our realities are layers of experiences intertwining with hopeful thoughts, which not necessarily exists after all. Our reality might not be what we perceive, but only what the eyes allow us to see as we can be fooled into looking only at the surface of things. Summer Thoughts brings me to the visual colors of eternal happiness. Hopeful thoughts that rely on the optimism of the uncertain future, and championing our daily struggles against the ups and downs of broken emotions as colors are nutrients to the mind, and playful textures are humor to the soul.